2016
DOI: 10.1136/annrheumdis-2015-209068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ustekinumab in psoriatic arthritis patients with peripheral arthritis and physician-reported spondylitis: post-hoc analyses from two phase III, multicentre, double-blind, placebo-controlled studies (PSUMMIT-1/PSUMMIT-2)

Abstract: PSUMMIT-1 (NCT01009086, EudraCT 2009-012264-14) and PSUMMIT-2 (NCT01077362, EudraCT 2009-012265-60); post-study results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 21 publications
0
73
0
7
Order By: Relevance
“…It has also shown benefit in AS in an open-label study30 and a separate post hoc pooled analysis 31. Intriguingly, and in direct contrast to IL-17A blockade, ustekinumab is effective in CD with evidence for a prolonged benefit following a single infusion 32 33.…”
Section: The Th17 Axismentioning
confidence: 99%
“…It has also shown benefit in AS in an open-label study30 and a separate post hoc pooled analysis 31. Intriguingly, and in direct contrast to IL-17A blockade, ustekinumab is effective in CD with evidence for a prolonged benefit following a single infusion 32 33.…”
Section: The Th17 Axismentioning
confidence: 99%
“…Additional composite measures, determined post hoc employing component data available from preplanned study assessments, included the Psoriatic ArthritiS Disease Activity Score (PASDAS), the Disease Activity in Psoriatic Arthritis (DAPsA) score, and the Clinical Disease Activity Index (CDAI). The PASDAS [20,21] was calculated using patient global disease activity VAS (arthritis and psoriasis), physician global disease activity VAS, 68-joint TJC, 66-joint SJC, CRP, enthesitis (LEI), dactylitis (scores of 0-3 recoded to 0-1, where any score > 0 equaled 1; range, 0-20) [22], and the physical component summary score of the 36-item Short Form Health Survey [23]. Disease activity cutoffs were remission (≤ 1.9), low (> 1.9-< 3.2), moderate (≥ 3.2-< 5.4), and high (≥ 5.4) [24].…”
Section: Clinical Assessments and Composite Endpointsmentioning
confidence: 99%
“…Inhibition of IL-12 and IL-23 leads to an inhibition of Th1 and Th17 T‑cells leads to an inhibition of important inflammatory pathways in PsA [36]. In phase 3 trials ustekinumab especially showed improvement in skin disease but other factors, such as enthesitis, dactylitis, nail disease, physical function and quality of life also improve [42]. Another new therapeutic agent is secukinumab, a human monoclonal IgG1k antibody, targeting IL-17A, which also has a proinflammatory role in the pathophysiology of PsA.…”
Section: Novel Treatment Targetsmentioning
confidence: 99%